A study of the thermodinical properties of ethanol: an analysis based on data from the literature - Moura, Luiz Eduardo Freitas de; Soares, Victoria Victor; Chiavone Filho, Osvaldo (Brazilian Journal of Production Engineering, 2024)
This article aimed to analyze the thermodynamic parameters, calorimetric and volumetric data, of ethanol (CH2COH), a substance widely used industrially. The methodology included collecting data from articles using NIST and Periódicos Capes tools, followed by insertion into Excel for prediction and statistical calculations. Software such as Peng-Robinson and DDB were used to obtain experimental data. The Origin application was used to calculate errors and discrepancies in relation to references. Furthermore, models such as the Antoine equation, Rackett equation and polynomial regression were used to determine coefficients and calculate heat and volumetric capacities. The results indicated good adaptation of the proposed models to the experimental data, with average errors varying between 0.039% and 22.8%. It was concluded that the determination of thermodynamic aspects is crucial for industry and academic training, predicting the behavior of chemical substances.
Keywords: Thermodynamics; Thermodynamic parameters; Ethanol